The Old Bulgarian capital Tărnovo according to George Akropolites - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2025)
The article is dedicated to an analysis of the image, role, and significance of the late medieval Bulgarian capital, Tărnovo, as presented in the historical work of George Akropolites. For him Tărnovo emerges as the most important city of interest located within the central territories of the Bulgarian Tsardom, enclosed between the Danube River and the Balkan Mountains. It was the permanent residence of the tsar’s family and the Bulgarian court. Tărnovo was also the religious center of the Bulgarian Orthodox Church, the seat of its ecclesiastical head. The capital hosted royal coronations, marriages, and high-level diplomatic encounters. Often, members of the royal family met their deaths there and were buried in the city. High-ranking foreign captives were imprisoned and held within its walls. The city served as a gathering point for the Bulgarian army prior to military campaigns. Foreign envoys traveled to it, and tsar’s legates departed from and returned to it. Tărnovo also functioned as the central arena in the struggle for power within the Bulgarian Tsardom – a place of intrigue, conspiracy, and a target of external aggression. An analysis of Akropolites’ testimony demonstrates that control over the capital was a prerequisite for exercising legitimate authority in Bulgaria and over the Bulgarians.